2013
DOI: 10.1098/rsif.2013.0717
|View full text |Cite
|
Sign up to set email alerts
|

Contact inhibition of locomotion probabilities drive solitary versus collective cell migration

Abstract: Contact inhibition of locomotion (CIL) is the process whereby cells collide, cease migrating in the direction of the collision, and repolarize their migration machinery away from the collision. Quantitative analysis of CIL has remained elusive because cell-to-cell collisions are infrequent in traditional cell culture. Moreover, whereas CIL predicts mutual cell repulsion and 'scattering' of cells, the same cells in vivo are observed to undergo CIL at some developmental times and collective cell migration at oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 63 publications
20
123
0
Order By: Relevance
“…3). Previous studies reported that the centrosome in polarized motile cells is highly related to the directional cell migration but its location varies depending on cell type (Danowski et al, 2001;Desai et al, 2013;Niu et al, 1997;Pouthas et al, 2008;Ueda et al, 1997;Yvon et al, 2002), contact inhibition (Desai et al, 2013) and physical constraint (Jiang et al, 2005); our group recently demonstrated that MTOC position was highly correlated with cell polarization: the distance between MTOC and cell centroid was larger in polarized single cells (Hale et al, 2011). Consistent with the observation using EGFP-a-tubulintransfected cells (Fig.…”
Section: Distinct Nuclear Movements Synchronize With Cell Polarizationsupporting
confidence: 77%
“…3). Previous studies reported that the centrosome in polarized motile cells is highly related to the directional cell migration but its location varies depending on cell type (Danowski et al, 2001;Desai et al, 2013;Niu et al, 1997;Pouthas et al, 2008;Ueda et al, 1997;Yvon et al, 2002), contact inhibition (Desai et al, 2013) and physical constraint (Jiang et al, 2005); our group recently demonstrated that MTOC position was highly correlated with cell polarization: the distance between MTOC and cell centroid was larger in polarized single cells (Hale et al, 2011). Consistent with the observation using EGFP-a-tubulintransfected cells (Fig.…”
Section: Distinct Nuclear Movements Synchronize With Cell Polarizationsupporting
confidence: 77%
“…14, 18, 45); (ii) velocity alignment (VA), in which cells align their polarity to their own velocity (13,15,47,48); (iii) contact inhibition of locomotion (CIL), in which cell polarity is inhibited by contact with other cells (10,12); and (iv) cell front-front inhibition (FF), a generalization of CIL in which only contact with the cell front is inhibitory. FF is supported by experiments of Desai et al (49) that show head-head collisions lead to repolarization at a greater rate than head-tail collisions. There is also some historical precedent; in early papers on CIL, Abercrombie and Dunn (44) argued for a distinction between head-head and head-tail collisions; see also ref.…”
Section: Rotational Motion Is Strongly Regulated By Cell Polarity Mecsupporting
confidence: 71%
“…The mechanisms of CIL and FF are very similar and may be difficult to distinguish from unconstrained collision data (5). In adhesive stripe assays, collision statistics are simpler to obtain (43, 49); Desai et al (49) note that head-tail collisions are less likely to lead to repolarization of both cells, consistent with FF rather than our CIL mechanism. However, other mechanisms, such as VA, could also lead to both PRM and asymmetry between head-head and head-tail collisions.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequently, repolarization of the cell's cytoskeleton creates a new front away from the adhesion zone, and the two cells thus separate (20,21). This interaction has been shown to be crucial in determining the collective behavior of cell groups in several contexts (22). For example, CIL guides the directional migration of neural crest cells (23) and also ensures the correct dispersion of Cajal-Retzius cells in the cerebral cortex (24) or of hemocytes in the embryo (25).…”
mentioning
confidence: 99%